MOBILITY OF THREE HERBICIDES IN TWO DIFFERENTSOIL TEXTURES - Barbosh, Mowafaq (Iraqi Journal of Science, 2025)
This research carried out to estimate mobility three herbicides (Basta٢٠%, Weedoff ٤٨%, Carbyne ١٢.٥%) it might be reach on water table andpolluted it. We definite the mobility by hydraulic conductivity it depends onliquid and soil feature.The samples collected from two locations Kefel was first one sandy soilbelonged to Orthids group and second one was Mishkab clay soil belongedto Torrifluvents group. Soil columns had been prepared by three replicates toeach one. So the H.CO determinated with constant head method to sandysoil and variable hydraulic gradient to clay soil. The H.CO measures madeby two stages: ١-First stage treatments (٣ soil herbicides vs control)٢- Second stage treatment (٣ soil + herbicides + drying vs control).The results analysised by C.R.D. design with Dunnett's method to meancomparison it were :Carbyne > Water > Basta > Weedoff in sandy soilWater > Weedoff > Basta > Carbyne in clay soilIt refers to Carbyne herbicide mobile by H.CO(٠.٥٧) cm.min-١ withsignificant deference (D٠.٠٥ = ٠.١٢) vs other . It might be reach on watertable as well as Weedoff succeeded by H.CO (٠.٠٥) cm.min-١ with (D٠.٠٥ =٠.١٢٢) vs others but that meant no risky than H.CO of control.